Informationization of small-scale agribusinesses in rural areas of Korea: Perspectives from institutional theory. (September 2016) - Kang, Chunghan; Hwang, Yoonmin; Moon, Junghoon
Despite the significance of IT for small-scale agribusinesses (SSAs) in rural areas, little work has been done to identify the determinants of their informationization. Prior studies also overlook the social influences of informationization among SSAs in rural areas. Therefore, this study presents a model to explore and describe the roles played by institutional forces in the informationization of rural SSAs. To empirically test the presented model, partial least squares (PLS) analysis was conducted using the survey responses of 180 ginseng farmers. The results show that mimetic forces related to other farmers' successful adoption and usage of IT positively affect states of informationization and intentions towards future informationization among rural SSAs. Innovative SSAs are less likely to be affected by these forces, and normative forces from partners and customers are positively related to states of informationization. For the government, the results suggest that policy interventions should focus on mimetic forces rather than coercive forces to aid in creating more effective SSAs and foster rural development.